2019
DOI: 10.4238/gmr18258
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genomic association study for age at first calving and calving interval in Romosinuano and Costeño con Cuernos cattle

Abstract: Inheritance of fertility traits in cattle is complex since they are controlled by multiple loci. Genome-wide association studies are an efficient tool to detect genomic regions that explain the phenotypic variation for a trait of interest. The aim of this study was to identify genomic regions that affect the age at first calving (AFC) and the calving interval (CI) in the Romosinuano (ROMO) and Costeño con Cuernos (CCC) creole cattle breeds and nominate candidate genes that influence these reproductive traits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Some of the genes located in at least two different metrics were considered as relevant genes for further investigation. For instance, some of these genes are related to heat shock proteins (e.g., DNAJB13 ), oxygen transport (e.g., HBB and HBG ; Neupane et al, 2017 ), mitochondrial DNA maintenance (e.g., PIF1 ; Foury and Kolodynski, 1983 ), metabolic activity (e.g., HSPE1 ; Kumar et al, 2015 ), feed intake (e.g., SNORA70 ; Pitt et al, 2018 ), carcass conformation (e.g., SNORA70 ; Pitt et al, 2018 ; PLCL1 ; Shin et al, 2015 ), fertility and reproduction traits (e.g., RBPMS2 , OAZ2 ; Fernández et al, 2019 ; IL6ST ; Song et al, 2009 ; IGSF8 ; Glazar and Evans, 2009 ), and olfactory receptors (e.g., OR51A7 ; Olivieri et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the genes located in at least two different metrics were considered as relevant genes for further investigation. For instance, some of these genes are related to heat shock proteins (e.g., DNAJB13 ), oxygen transport (e.g., HBB and HBG ; Neupane et al, 2017 ), mitochondrial DNA maintenance (e.g., PIF1 ; Foury and Kolodynski, 1983 ), metabolic activity (e.g., HSPE1 ; Kumar et al, 2015 ), feed intake (e.g., SNORA70 ; Pitt et al, 2018 ), carcass conformation (e.g., SNORA70 ; Pitt et al, 2018 ; PLCL1 ; Shin et al, 2015 ), fertility and reproduction traits (e.g., RBPMS2 , OAZ2 ; Fernández et al, 2019 ; IL6ST ; Song et al, 2009 ; IGSF8 ; Glazar and Evans, 2009 ), and olfactory receptors (e.g., OR51A7 ; Olivieri et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the limitation of the ascertainment bias and reduced genomic coverage of the SNP dataset used, an interesting list of potential genes under selection in multiple cattle breeds, YAK, and BLI, which will be the foundation for future investigations could be still provided. For instance, the RBPMS2 gene, found in YAK is related to age at first calving in Romosinuano and Costeño-con-Cuernos cattle breeds ( Fernández et al, 2019 ) and the gene ATG16L2 found in MG cattle is related to mastitis recovery in Danish HOL cows ( Welderufael et al, 2017 ). Angrecka and Herbut (2016) observed that cows in excessive cold temperatures may show fertility impairments and the potential candidate gene RBPMS2 found in YAK might be an indication of adaptation for the cold environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein coded by IDH3A was up regulated in the ovaries of post-pubertal heifers as compared to pre-pubertal heifers [ 96 ]. The gene PTGDR was within a peak SNP region in this study and had been reported as a candidate in a previous GWAS as associated with age at first calving in cattle [ 97 ]. In short, these candidate genes suggested by peak SNPs have supporting evidence from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two other SNP suggestively associated with BL, rs109186122 and rs43616983, are located in the genes GYPC and SLC16A4, respectively. According to its annotation in DAVID, GYPC is involved in oligosaccharide binding and is reported to be associated with intramuscular fat deposition and reproduction performances in cattle [117][118][119]. The SLC16A4 gene had effects on postweaning weight gain, feed efficiency and resistance to the bovine viral diarrhea virus in cattle [120][121][122].…”
Section: Body Length and Ear Lengthmentioning
confidence: 99%